Development and Performances of Non-Phosphorus Corrosion and Scale Inhibitor - Chen, Yanmin; Sun, Caixia; Wu, Jinying; Huang, Changshan; Xu, Huiwu (Asian Journal of Chemistry, 2014)
One novel non-phosphorus multi-component composite water treatment agent was developed from polyepoxysuccinic acid, polyaspartic acid, polyacrylic acid and benzotriazole. The performances of scale and corrosion inhibition were evaluated by bubble experiments, rotary hanging-piece corrosion tests and electrochemical. The corrosion testing piece was characterized by SEM. The results showed that the new non-phosphorus composite water treatment agent had good performance of scale and corrosion inhibition. Further potentiodynamic polarization curves also indicated that the water treatment agent acted as a cathodic polarization-based suppression of mixed-type inhibitor.